Cross-dimensional network of democracy promotion: public administration reform in post-Euromaidan Ukraine. Issue 7 (3rd October 2021) - Samokhvalov, Vsevolod; Strelkov, Alexander
ABSTRACT: The article seeks to explain why the restructuring of the Ukrainian public administration – a key element in democracy promotion – has been patchy, in spite of EU's substantial investment in the reform process. On the basis of analyzing EU and Ukrainian documents as well as process-tracing and interviews with stakeholders, the paper highlights limitations of explaining the outcome of Ukrainian civil service reform exclusively through functional cooperation, structural factors or civil society mobilization. Drafting and passing new public administration legislation was impossible without civil society mobilization; high-level intergovernmental pressure or functional cooperation would not have been able to achieve this on their own. Subsequent challenges with the implementation process show that the active involvement of civil society does not automatically lead to effective reform. Ultimately, it is the collaboration – often across informal channels – between high-level diplomats and state-representatives, actors involved in functional cooperation and civil society activists that makes reform possible.